Peran Organisasi Internasional dalam Pemulihan Ekonomi Pasca Covid-19 - Suci Edelwes Harahap; Nursalamah Nursalamah; Edison Siregar; Arsidin Batubara (Journal of Islamic Economics and Finance, 2024)
Economic recovery is the initial part of expansion, where the economy regains its strength to grow after the recession. Economic growth shows signs of strengthening, if managed and carried out with the right strategies and policies by each State. The purpose of the study is to analyze the policies of international organizations in economic recovery after the COVID-19 pandemic. This research uses a descriptive qualitative method by means of literature research. The results obtained in this study are that international organizations have done a lot of research and sparked policies to help the global economic recovery.